Teaching theory of literature in Spain - Navas Ocaña, Isabel (Tropelías: Review of Literary Theory and Comparative Literature, 2020)
The main goal of this paper is to offer an overview of Literary Theory and Comparative Literature studies in Spanish Universities since the eighties, when this area was created. The new subjects that have arisen as a consequence of the different curricula along these years, and especially as a consequence of the implementation of the European Higher Education Area, will be subject to analysis and reflection, as well as the relevance that TIC has recently reached in teaching and learning processes of Literary Theory and Comparative Literature.
Keywords: Theory of Literature; Comparative Literature; Didactics